The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3847/0004-637x/822/1/8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perchlorates on Electron Radiolysis of Glycine With Application to Mars

Abstract: This work explores the radiolytic decomposition of glycine (H 2 NCH 2 COOH) under simulated Martian conditions in the presence of perchlorates (-ClO 4), which are abundant oxidizers on the surface of Mars, by energetic electrons at 10, 160, 210, and 260 K, mimicking the radiation exposure of the Martian regolith in the first 5-10 cm depths over about 250 million years. Our experiments present quantitative evidence that the rate constants of the glycine decomposition in the presence of magnesium perchlorate hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 91 publications
2
16
1
Order By: Relevance
“…By knowing the volume of the solution added onto the substrate, the average density and area of the solid sample and the average sample thicknesses could also be calculated. The samples were prepared by utilizing the method established in our previous work (Góbi et al 2016a). Briefly, pure adenine (for the neat adenine samples) or adenine with Mg(ClO 4 ) 2 •6H 2 O in a 1:1 molar ratio (for the adenine-Mg (ClO 4 ) 2 •6H 2 O 1:1 mixture samples) were dissolved in distilled water (H 2 O), then 0.250-0.390 ml of these solutions (Table 2) was placed onto the surface of the silver substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By knowing the volume of the solution added onto the substrate, the average density and area of the solid sample and the average sample thicknesses could also be calculated. The samples were prepared by utilizing the method established in our previous work (Góbi et al 2016a). Briefly, pure adenine (for the neat adenine samples) or adenine with Mg(ClO 4 ) 2 •6H 2 O in a 1:1 molar ratio (for the adenine-Mg (ClO 4 ) 2 •6H 2 O 1:1 mixture samples) were dissolved in distilled water (H 2 O), then 0.250-0.390 ml of these solutions (Table 2) was placed onto the surface of the silver substrates.…”
Section: Methodsmentioning
confidence: 99%
“…A later work also found an alternative pathway resulting in chlorine dioxide (ClO 2 ) aside from oxygen, which may further accelerate the decomposition of organics as it is an even more proficient oxidant (Góbi et al 2016b). It has also been previously shown that two parallel decay mechanisms coexist when amino acids are irradiated in the presence of magnesium perchlorate hexahydrate (Mg(ClO 4 ) 2 •6H 2 O): the radiolytic decomposition of the organic molecule by the energetic electrons and the oxidation of the molecule and its irradiation products by oxygen formed upon the irradiation of neighboring perchlorate units (Góbi et al 2016a). It is important to note that the most stable form of magnesium perchlorate under Martian conditions is hexahydrate (Chevrier et al 2009;Toner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This finding may suggest that they can also oxidize sensitive molecules upon irradiation of energetic particles, which contributes to the lack of organics on the Martian surface. Laboratory experiments have provided compelling evidence that even complex organic molecules such as amino acids like glycine (H 2 NCH 2 COOH, Góbi et al 2016) can be oxidized efficiently in the presence of oxidants such as perchlorates ( -ClO 4 ) exposed to ionizing radiation in the form of ultraviolet (UV) photons and energetic galactic cosmic-ray (GCR) particles in the Martian soil (Pavlov et al 2012). Although their overall energy flux is four orders of magnitude less than the energy flux of the solar photons (Pavlov et al 2012), GCRs are the most relevant agent in the destruction of the organics in the deeper layers of the Martian soil since UV photons are effectively absorbed within the first few microns of the soil (Muñoz-Caro et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be explained if the oxychlorine in Gale Crater is poorly crystalline, or its concentration is below the 1 wt% detection limit of CheMin, which means that the concentration of oxychlorine species may vary across the planet. Unfortunately, only a few studies have been reported in the literature about the effect of irradiation on the stability of organic molecules in the presence of perchlorates [136,137], while many studies have tried to reproduce the pyrolysis results of the Viking, Phoenix, and MSL missions (see Lasne et al [125], and references therein). Hydrogen peroxide has been detected so far only in the atmosphere of Mars, at levels ranging from 18 to a maximum of 40 part per billion (ppb), with seasonal variations depending on the abundance of atmospheric water vapor and water ice clouds [140][141][142].…”
Section: Oxidants On Marsmentioning
confidence: 99%